2018 IEEE International Ultrasonics Symposium (IUS) 2018
DOI: 10.1109/ultsym.2018.8579955
|View full text |Cite
|
Sign up to set email alerts
|

A Row-Column-Addressed 2D Probe with an Integrated Compound Diverging Lens

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It should also be noted that T l depends exponentially on the frequency. This parameter influences the shape of the frequency impulse response and causes a down-shift of the center frequency and a reduction in the bandwidth [16], [21]. The attenuation coefficient is also of the foremost importance for a high-frequency transducer as the signal can be completely damped at these frequencies.…”
Section: Designmentioning
confidence: 99%
“…It should also be noted that T l depends exponentially on the frequency. This parameter influences the shape of the frequency impulse response and causes a down-shift of the center frequency and a reduction in the bandwidth [16], [21]. The attenuation coefficient is also of the foremost importance for a high-frequency transducer as the signal can be completely damped at these frequencies.…”
Section: Designmentioning
confidence: 99%
“…Our group in Denmark has worked extensively with RC arrays for the last ten years within anatomic and functional imaging primarily based on synthetic aperture (SA) sequences. We have also fabricated a range of RC probes including PZT and CMUT based devices [41] and developed fabrication schemes for diverging lenses and probes with integrated lenses [42,43]. The various results and possibilities will be presented below.…”
Section: A History Of Row-column Imagingmentioning
confidence: 99%
“…The first 2D array using CMUTs based on the row-column addressing scheme had 32+32 elements fabricated using wafer fusion bonding, where the cavities and membranes were both made with silicon nitride. Since then several row-column CMUTs have been designed and fabricated with a variety of different methods, such as sacrificial release [37], [38] using a TOBE array architecture, adhesive wafer bonding [39], [40], fusion bonding [16], [41]- [44] and anodic bonding [45]- [47]. Some of these arrays have been integrated in hand-held probes, presented in [16] as a 62+62 RCA 2D CMUT probe together with a corresponding PZT probe for comparison, and in [44] where two 92+92 RCA 2D CMUT probes with and without integrated diverging lenses are presented.…”
Section: B Capacitive Micromachined Ultrasonic Transducersmentioning
confidence: 99%
“…Since then several row-column CMUTs have been designed and fabricated with a variety of different methods, such as sacrificial release [37], [38] using a TOBE array architecture, adhesive wafer bonding [39], [40], fusion bonding [16], [41]- [44] and anodic bonding [45]- [47]. Some of these arrays have been integrated in hand-held probes, presented in [16] as a 62+62 RCA 2D CMUT probe together with a corresponding PZT probe for comparison, and in [44] where two 92+92 RCA 2D CMUT probes with and without integrated diverging lenses are presented. These probes showed the potential for using CMUTs for RCA arrays and demonstrated that such probes can attain similar performances as a PZT probe made using the same dimensions.…”
Section: B Capacitive Micromachined Ultrasonic Transducersmentioning
confidence: 99%